RANCANG BANGUN SISTEM INFORMASI PENJUALAN DI TOYOTA AUTO 2000 PT. ASTRA INTERNASIONAL Tbk BANDUNG - Rini Suwartika Kusumadiarti; Rian Taufik Muttaqin (POLITEKNIK PIKSI GANESHA, 2019)
Selling is the science and art of personal influence that is carried out personally by the seller to invite others to be willing to buy the goods and services offered.The research method used is the Waterfall method. Data collection techniques used through observation, interviews and literature reviews related to the main problem. From the research conducted, found the problem that the car sales data processing system in cash and credit is still less efficient. Based on these problems, we need an information system that can facilitate the management of car sales data. The suggestions given are: (1) Replacing manual systems with computerized systems, (2) Conducting regular program maintenance, (3) Conducting training for users in running applications, and (4) Developing programs in the future